The Relationship between Student Perceptions of Teaching Style and Teachers' Emotional Intelligence and Motivation Learn PAI class XI MAS Al Imron - Julkasi Ady Sahala Matondang; Yusnaili Budianti; Muhammad Rifai (Didaktika: Jurnal Kependidikan, 2024)
This research aims to determine whether there is a relationship between students' perceptions of the teacher's teaching style and students' PAI learning motivation and whether there is a relationship between the teacher's emotional intelligence and students' PAI learning motivation and whether there is a joint relationship between students' perceptions of teaching styles and emotional intelligence. teachers with motivation to learn PAI. This type of research is quantitative descriptive correlational. The sample was taken from 20% of the 180 population in all class XI, representing 36 students. The data collection tool uses a questionnaire in the form of a Likert scale. The results of the research show that students' perceptions of teachers' teaching styles and teachers' emotional intelligence have a relationship with students' learning motivation in Grade 11 Islamic Religious Education among MAS AL IMRON students, Kec. Ujung Batu, North Padang Lawas Regency. In testing the research hypothesis, the correlation obtained (1) (2) correlation of X2 with Y = calculated r value is greater than table r value (0.996>0.329) and siqnification value is smaller than 0.05 (0.016<0.05). (3) The correlation of X1 and This is also shown by the correlation value or R of 0.996 which is greater than the r table (0.996>0.329). This means that the results of data analysis show a relationship between the three variables with a significant level of 95%